MANAJEMEN PESERTA DIDIK DALAM PERSPEKTIF PENDIDIKAN ISLAM - Diana, Erlin; Naisila; Kamila, Siti K.; Maryati, Sulis (Sindoro: Cendikia Pendidikan, 2024)
Management is a set of activities or processes of managing the use of resources, in order to achieve the main predetermined goals by using people in a cooperative relationship. Islamic education management consists of three words, namely management, education, and Islam. Although this study is not explicitly described in the Qur'an, However, there are some cues that show how important the selection of educational environment is. Learner management is an integral part of modern educational management. This covers various important aspects in the management of students, from planning to evaluation, then the approach in Islamic management, the right approach will certainly lead to the right expectations and goals, among others with the student management approach, namely: 1. The quantitative approach, 2. The qualitative approach. 3. Integrated Approach. In general, student management aims to organize various activities in the field of student affairs so that learning activities in schools are carried out smoothly, orderly and regularly, as well as the achievement of educational goals in schools.